Different ethical perspectives justifying reasonings behind a person’s actions: a case study on a private institution in Malaysia - Diyana, Kamarudin; Haziman, Zakaria; Azizan, Azit (Universiti Malaysia Pahang, 2020)
Private institutions in Malaysia are bound to the Private Higher Institution Act 1996 which normally relies on corporate investments to sustain their operations. Data from the Department of statistic Malaysia indicates that there is a significant increment of gross output value in the education sector in Malaysia from RM 17.6 billion in 2017 compared to RM 15.2 billion in 2015 which reflects the business competencies in private institutions (Ministry of Education Malaysia, 2015). This research is a case study conducted at one of the private colleges in Kuantan, Pahang. The aim of this research is to analyze the ethical issues concerning business ethics using semi structure interview method with college staff and students. The interviews were recorded and transcribed. Each case was analyzed individually, discussed and linked to the business ethics concept and ethical principle. This research aims to create awareness on good moral value and business ethics that can be practiced in the private education sector in Malaysia.